Rekonstrukcja strategii Stanów Zjednoczonych wobec Tajwanu podczas prezydentury Josepha Bidena (Politeja, 2023)
RECONSTRUCTING THE US STRATEGY TOWARDS TAIWAN DURING THE PRESIDENCY OF JOSEPH BIDENAdopting the model of neoclassical realism and elements of the American-centric nationalist paradigm, the paper examines both systemic factors stemming from the Sino-American power rivalry and internal ones referring to the populist traditions of American foreign policy. The main goal of America regarding Taiwan was to use its relationship with the island in its policy of containment of China by emphasizing Taiwan’s right to decide its future and preventing China from taking over the island by force. Along with deepening bilateral cooperation, the administration used multilateral mechanisms to promote the concept of peace and security across the Taiwan Strait as an essential element of the global order, which increased the number of countries interested in maintaining the status quo. Russia’s aggression against Ukraine heightened concerns about the possibility of PRC’s attack on Taiwan, prompting the Biden administration to intensify pressure on Taipei to accelerate military reform. However, the accentuation of closer relations between Washington and Taipei was interpreted by China as a provocative crossing of more “red lines,” leading to an intensification of repressive measures against Taiwan and the consolidation of bellicose rhetoric directed against both Washington and Taipei.